2017
DOI: 10.1002/1878-0261.12049
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of uterine adenosarcomas and phyllodes tumors of the breast

Abstract: Uterine adenosarcomas and breast phyllodes tumors (PTs) are morphologically similar, being composed of stromal projections in a leaf-like fashion lined by epithelial cells. Here, we investigated whether their histologic similarities would be mirrored at the genetic level. The previously reported repertoires of somatic genetic alterations found in 19 adenosarcomas and 22 PTs (six benign, six borderline, and 10 malignant) were compared. PTs significantly more frequently displayed mutations affecting MED12, the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…There have also been documented reports on the presence of FA‐like areas in PTs , cases of synchronous FA and PT, along with patients with FA having subsequent PT after a period of time, albeit this remains a rare occurrence . Such findings support theories of both tumours sharing similar origin and aetiology, with recent studies unveiling their mutational and gene expression profiles .…”
Section: Introductionmentioning
confidence: 54%
“…There have also been documented reports on the presence of FA‐like areas in PTs , cases of synchronous FA and PT, along with patients with FA having subsequent PT after a period of time, albeit this remains a rare occurrence . Such findings support theories of both tumours sharing similar origin and aetiology, with recent studies unveiling their mutational and gene expression profiles .…”
Section: Introductionmentioning
confidence: 54%
“…A few studies demonstrated TERT promoter mutation in PT 7 , 10 , 11 , however, TERT protein expression in PT has not been studied. We observed TERT promoter mutation in 27% of the cases, which was lower than some reported studies (35–65%) 7 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Common somatic mutations affecting cancer associated genes, including TP53, RB1 and EGFR occur exclusively in high grade PTs 6 9 . In addition, frequent mutations in non-coding region of telomerase reverse transcriptase ( TERT ) promoter has also been described 7 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several less-characterized genetic alterations (e.g. in ATRX [ 16 , 17 ], BCORL1 [ 9 ], and ZNF217 [ 11 ]) whose role in the development and progression of PTs is unknown were identified. As alterations in those genes were rarely reported they are probably not one of the key drivers in the development of PTs.…”
Section: Introductionmentioning
confidence: 99%